(untitled) (Journal of Management and Social Sciences, 2021)
The general picture that seems to portray the female gender from the western perspective presents the oppressive image of women in society. On the contrary, despite cultural flow as a result of globalization, certain insinuations and indeed realities among the Yoruba of south-western Nigeria portray a privileged status for the female gender. “Iyaniwura” mothering is gold, in Yoruba society and indeed the world over shows the value attached to mothering. The psychological impression made on yet to be mothers prepares them for privilege statuses in spite of possible negative experiences in mothering. The value of gold is manifested in what mothers are to expect when their children grow. They are to be cherished, pampered and appreciated. The paper brings to the fore, how these play out in reality by adopting the qualitative method, using the In-depth interview technique to elicit information from young mothers about their expectations, concerning the saying ‘mothering is gold’ and mothers of married children on how real their mothering has been ‘golden’. This study tries to fill the gap by showing that mothering as a process of child caring and rearing, and motherhood as an institution is quite appreciated in the Yoruba society by mothers and children. Keywords Mothering, gold, margins, Yoruba, South-west